A new name for Gloriosa grandiflora (Colchicaceae) from the Democratic Republic of Congo (Kinshasa - Maroyi, Alfred; Maroyi, Alfred (Phytotaxa, 2014)
In a recent contribution, Vinnersten & Manning (2007) transferred Littonia Hooker (1853: t. 4723) species to Gloriosa Linnaeus (1753: 305), making 7 new combinations. Unfortunately, the combination Gloriosa grandiflora (De Wildeman & Durand 1901: 34) J.C.Manning & Vinnersten in Vinnersten & Manning (2007: 178) is illegitimate since it is preoccupied by Gloriosa grandiflora (Hooker 1860: t. 5216) O’Brien (1904: 188), now known as Gloriosa simplex Linnaeus (1767: 62) (Maroyi, 2012). We hereby correct this matter by providing a new epithet: